Danmarks Nationalbank's operating costs and number of employees in an international comparison - Erik Haller Pedersen (Danmarks Nationalbank, 2006)
The paper benchmarks Danmarks Nationalbank against a number of other central banks with respect to operating costs and the number of employees. The management of Danmarks Nationalbank historically has in general taken action at an early stage in the effort to optimise the organisation of the Bank. This has resulted in relative low costs and a lean organisation by international comparison, but it also implies that the scope for further cost reductions probably is smaller than in many other central banks. Staff costs, i.e. mainly salaries, are among the lowest for the central banks included in the assessment, and the lowest among the Nordic countries.
Keywords: E58; 330; central bank costs; central bank efficiency; Zentralbank; Benchmarking; Vergleich; Dänemark